PENGARUH METODE ROLE PLAYING TERHADAP KEMAMPUAN SISWA DALAM PEMAHAMAN ISI DONGENG DI SMP YAPIDA CISAYONG TASIKMALAYA - Elly Samrotul Fuadah; Heti Triwahyuni (Prodi Pendidikan Bahasa dan Sastra Daerah, 2017)
the result of research on the influence of methods Role Playing on the ability to understand the content fairytale Seventh Grade Students of SMP YAPIDA Cisayong Tasikmalaya. Abilty understand the contents of a fairy tale in the junior class VII YAPIDA Cisayong Tasikmalaya before using Method Role Playing result quite satisfactory, because it is different. The Role Playing method is used to improve the ability to understand the fairy tales of students applied in pretest and postes as